The Religious values Included in the Textbook of Tawheed for the sixth Grade Primary in Saudi Arabia: Content Analysis - Al - Maliki, Yahya Saad Damas (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the religious values ​​that should be included in the Textbook of Tawheed for the sixth grade in the Kingdom of Saudi Arabia.In order to achieve the objectives of the study, the method of content analysis of the Textbook of Tawheed was used for the second semester 2018 to answer the following questions: For the sixth grade primary in Saudi Arabia? The researcher developed a classification of the values ​​of faith in the study. He identified the system of faith values ​​in four main areas: (ideological values, worship values, values ​​of social transactions, and ethical values). The results of the study showed that the Textbook of Tawheed for the sixth grade in the Kingdom of Saudi Arabia includes the system of values ​​of faith in different fields with different rates and frequencies, and the total values ​​of faith extracted about (500) values, where the values ​​of belief ranked first at (31.00%) with average (155)), And the second rank was the ethical values at ​​(29.00%) with average (145) value. The third place was the social transactions at (22.00%) with average (110) value, The fourth rank is the ethical values at​​(18.00%) with average (90) value. The results indicate that there is no specific system for distributing these values ​​in the educational lessons that were included in the units of the Tawheed book for the sixth grade. The study recommends that the Tawheed book adopt a certain method of distributing the values ​​in parallel, taking into account the age of the students in the distribution of some different religious values
Keywords: Faith values; Kitab al-Tawhid; sixth grade of primary school; content analysis